ShenQiWan ameliorates renal injury in type 2 diabetic mice by modulating mitochondrial fusion and endoplasmic reticulum stress - Xiong, Wei; Feng, Jing; Liu, Yumeng; Liu, Jiapeng; Fu, Liang; Wang, Qian; Li, Xia; Li, Shuyu (Frontiers in Pharmacology, 2023)
Background: ShenQiWan is commonly used in traditional Chinese medicine for the treatment of diabetic nephropathy, which is closely related to mitochondrial fusion and endoplasmic reticulum stress. This study aimed to investigate the intervention effect and molecular mechanisms of ShenQiWan on renal injury in KKAy mice. Methods: C57BL/6J mice (11 weeks old) were fed a regular diet upon arrival, while KKAy mice (11 weeks old) were fed a high-fat diet upon arrival. At 12 weeks of age, KKAy mice with random blood glucose ≥13.9 mmol/L were identified as diabetic mice and randomly divided into the model group (n=30) and the treatment group (n=30),while C57BL/6J mice of 12 weeks old(n=30) served as the control group. The treatment group received daily aqueous decoction of ShenQiWan (13.5 g/kg), while the control group and model group received daily equal amounts of saline from 12 weeks old to 24 weeks old. The general status of mice was observed regularly, and fasting blood glucose and 24-hour urine microalbumin were measured. Ten mice were euthanized in each group at the age of 16, 20, and 24 weeks, serum samples were used for biochemical indexes and kidney tissues were used for morphological studies. GRP78, OPA1, MFN1, MFN2 mRNA and protein expression were detected by Real-time PCR, immunohistochemistry and Western-blot.The mice in the model group exhibited symptoms of lethargy, slow movement, obesity, polyuria and proteinuria. Morphological observation revealed pathological changes, including thickening of the glomerular basement membrane and interstitial fibrosis. After treatment with ShenQiWan, the fasting blood glucose level of KKAy mice was significantly reduced, urinary albuminuria was decreased, serum biochemical indexes were improved, renal tissue pathological changes were significantly alleviated. The results also showed a significant reduction in the expression of endoplasmic reticulum stress-related factor GRP78 and an increase in the expression of mitochondrial fusion-related factors OPA1, MFN1 and MFN2 after treatment with ShenQiWan. Conclusions: ShenQiWan can protect diabetic mice from renal damage by modulating mitochondrial fusion and alleviating endoplasmic reticulum stress, exerting its protective effects.